1991
DOI: 10.1128/aac.35.10.2016
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of cytokine production by macrolides: interleukin-6 production is increased by spiramycin and erythromycin

Abstract: Antibiotics do not act alone but act in conjunction with the host defense system. In pairticular, it has been shown that some antibiotics can modify cytokine production. We compared the in vitro effiects of three macrolides (roxithroinycin, spiramycin, and erythromycin) actively concentrated by leukocytes on interleukinla, (IL-la), IL-1p, , and tumor necrosis factor alpha. production by human monocytes stimulated with lipopolysaccharide. Our results show that the three macrolides tested have different effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Our in vitro studies revealed that CLI dose-dependently decreased TNF-␣ and IL-1␤ production and increased IL-6 production by macrophages. These results are similar to those obtained in in vitro studies where LPS-stimulated human monocytes were treated with fosfomycin (11) and erythromycin (1,5). In addition to the in vitro results, we confirmed that, in vivo, CLI modulated the induction of inflammatory cytokines through its action on peritoneal macrophages as one of the target cells.…”
supporting
confidence: 79%
“…Our in vitro studies revealed that CLI dose-dependently decreased TNF-␣ and IL-1␤ production and increased IL-6 production by macrophages. These results are similar to those obtained in in vitro studies where LPS-stimulated human monocytes were treated with fosfomycin (11) and erythromycin (1,5). In addition to the in vitro results, we confirmed that, in vivo, CLI modulated the induction of inflammatory cytokines through its action on peritoneal macrophages as one of the target cells.…”
supporting
confidence: 79%
“…Di erences in the level of several cytokines in the culture supernatant from wild-type Tax1 expressing PBL and mutant 703 expressing PBL was detected prior to the appearance of signi®cant di erence in the CD4+ cell population (Akagi et al unpublished data). In this context, it is worth mentioning that many Taxinducible cytokine genes have motifs of CRE or AP-1, which are activated indirectly by SRF, in combination with NF-kB in the promoter region (Bailly et al, 1996;Curtiss et al, 1996;Himes et al, 1993;Mori and Prager, 1996;Mori et al, 1994b;Yamashita et al, 1994). Full activation of these cytokine gene promoters might only be achieved by wild-type Tax1.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to IL-1, it is known that this cytokine increases the survival rate of mice systemically infected with P. aeruginosa (21). Recently, Bailly et al have reported that EM increased IL-6 production by human monocytes in vitro (4). Therefore, it is possible that EM possesses a lot of immunopotentiating effects, including the enhancement of cytokines production, and subsequently enhances the host defense system.…”
Section: Discussionmentioning
confidence: 99%